UPAYA PENINGKATAN HASIL BELAJAR SPEAKING DAN MINAT BELAJAR SISWA MELALUI METODE DEMONSTRASI PADA MATA PELAJARAN BAHASA INGGRIS - Misbah Fikrianto; Haryati Haryati (Akademika : Jurnal Teknologi Pendidikan, 2023)
This study aims to find out whether the Demonstration Method can improve Student Speaking Learning Outcomes, find out whether the use of the Demonstration Method can increase Student Learning Interest, find out how learning activities during learning activities use the Demonstration Method. The research method used is the Classroom Action Research method, which is a study conducted in the classroom, in which researchers study and reflect collaboratively on a learning approach with the aim of improving the process and results of teaching in the classroom through improvement. The results of the research and discussion draw the conclusion that the application of the demonstration method can increase students' learning interest. The results showed that the demonstration method created a pleasant learning atmosphere so that student learning outcomes increased, namely from cycle 1 to cycle 2 and to cycle 3 there was an increase, cycle 1 the average student learning outcomes were 35%, student activity was 37.5% and student learning interest 64%. In Cycle 2 there was an increase but it was not satisfactory, increasing to 65%, student activity 59% and learning interest to 78.7%. Cycle 3 is the end of the research, the average value of students has reached the expected value, the acquisition value is 85%, learning activities are 86% and learning interest has increased to 81%. It was concluded that the demonstration method can improve the learning outcomes of speaking English because with this method students learn as if they are faced with daily activities, students learn and practice.